Reverse Cholesterol Transport: Molecular Mechanisms and the Non-medical Approach to Enhance HDL Cholesterol - Marques, Leandro R.; Diniz, Tiego A.; Antunes, Barbara M.; Rossi, Fabrício E.; Caperuto, Erico C.; Lira, Fábio S.; Gonçalves, Daniela C. (Frontiers in Physiology, 2018)
Dyslipidemia (high concentrations of LDL-c and low concentrations of HDL-c) is a major cause of cardiovascular events, which are the leading cause of death in the world. On the other hand, nutrition and regular exercise can be an interesting strategy to modulate lipid profile, acting as prevention or treatment, inhibiting the risk of diseases due to its anti-inflammatory and anti-atherogenic characteristics. Additionally, the possibility of controlling different training variables, such as type, intensity and recovery interval, can be used to maximize the benefits of exercise in promoting cardiovascular health. However, the mechanisms by which exercise and nutrients act in the regulation of cholesterol and its fractions, such as reverse cholesterol transport, receptors and transcription factors involved, such as PPARs and their role related to exercise, deserve further discussion. Therefore, the objective of this review is to debate about non-medical approaches to increase HDL-c, such as nutritional and training strategies, and to discuss the central mechanisms involved in the modulation of lipid profile during exercise, as well as that can be controlled by physical trainers or sports specialists in attempt to maximize the benefits promoted by exercise. The search for papers was performed in the databases: Medline (Pubmed), Science Direct, Scopus, Sport Discus, Web of Science, Scielo and Lilacs until February 2016.